Implantação do sistema de gestão ambiental em uma universidade pública no Rio Grande do Sul, Brasil - Sgarbi, Márcio (2013)
Initiatives for environmental preservation have been taken since the 60s since the consequences of human negative impacts on the environment have been reported. Global conferences, discussions and publicity have made this issue gradually more relevant for the news and, more importantly, for the political agenda. Nowadays, in Brazil, for example, both government projects like A3P and regulatory instructions such as ABNT NBR ISO 14001: 2004 are crucial to reduce environmental damage caused by humans. Federal University of Rio Grande do Sul developed a tool called LAIA (an acronym, in Portuguese, for environmental aspect and impact analysis) to help implementing an environmental management system which includes concepts from ISO 14001: 2004 and adaptations of FMEA - a tool that is frequently used in automotive industry. Diagnosis were made on university buildings as to their environmental possible impacts and then action plans known as 5W2H were developed as part of the environmental management system. To represent the environmental performance analysis, 12 units were selected and 4 of them have gone through, at least, three LAIA cycles. By applying the Total Environmental Risk Index, we reported a decreasing trend in environmental risk for the studied units since there were, at least, three index measurements for each unit with a descending sequence over time. LAIA tool was efficient because it could suit to any diagnosed situation so far without losing analysis quality. Thus, the tool can be used in other institutions with different structures, procedures and products.